Thermal Shock Resistance of Precursor Derived Si-Hf-C-N(O) Foams. Issue 2 (3rd April 2019) - Sridar, Soumya; Awin, Eranezhuth Wasan; Kousaalya, Adhimoolam Bakthavachalam; Kumar, Ravi
ABSTRACT: Thermal shock resistance of precursor derived Si-Hf-C-N(O) foams at temperatures varying from 800o-1000oC subjected to multiple thermal cycles was investigated. The as-synthesized foams possessed interconnected pores with an average cell size of 1.09 mm. The X-ray diffractograms of the foams before and after thermal cycling showed that the amorphous nature of the foams was retained. FTIR spectra exhibited that there was no change in the bonding characteristics due to thermal shock. A damage parameter ( D S ) based on the compressive strength was used to quantify the extent of damage. Densification was expected to occur in the first thermal cycle and the strut structures did not show any sign of cracking. However, cracking of struts occurred in the third thermal cycle which caused severe damage. GRAPHICAL ABSTRACT: